Risk Identification of Public Private Partnership Contracts with The Build-Operate-Transfer Scheme on Toll Road in Indonesia - Panggabean, J Burju Ferdinand; Riantini, Leni Sagita; Setyawati, Rahayu (International Journal for Disaster and Development Interface, 2024)
One of the most crucial things that every nation needs is infrastructure. To boost the nation’s competitiveness, the Indonesian government is expediting infrastructure construction. Howeve, there are risk and big financial outlays that need to be addressed. A collaboration agreement, often known as public-private partnership (PPP), between the government and the private party is required in order to do this. With this contract, the government will be able to increase the number of toll roads throughout Indonesia. Although PPP comes in a variety of forms, the Build Operate Transfer (BOT) model is the most commonly used. The organizers and managers of the toll road will assume the government may be able to increase the number of toll roads Indonesia requires with the help of this deal. Although PPP comes in a variety of forms, the BOT model is the most commonly used. The organizers and managers of the toll road will assume all risks associated with the partnership plan. In order to reduce the risks caused by a partnership, each risk must be identified, assigned, and given the proper reaction. The data used in this study comes from BOT cooperation scheme-using toll road projects. The study indicates that there are relevant risks for toll road projects in Indonesia using PPP contracts with the BOT scheme, (1) political risk, (2) feasibility study risk, (3) financial risk, (4) design risk, (5) construction risk, (6) operation risk, and (7) transfer risk. The risk allocation in this research is based on expert opinions, adapted from ongoing toll road BOT projects in Indonesia.